The Development Of Islamic Education Curriculum On Building Religious Moderation At Manbaul Ulum Islamic Boarding School - Dumiyati Dumiyati; Aries Musnandar; Julhadi Julhadi; Zaedun Na’im; Muta'allim Muta'allim (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Manbaul Ulum Islamic boarding school is a classical Salaf educational institution that develops its educational curriculum based not only on nushus sharia but also on maqashidus sharia. Technically, the curriculum development is oriented towards the construction of the character of tawazun, i'tidal, and tawassuth in religion. The research on the development of a religious moderation curriculum is of utmost importance because it aims to prevent extremism, enhance understanding and tolerance among different religions, and instill ethical and moral values within the religious context. This study aims to explore the development of an Islamic education curriculum in building religious moderation in the Islamic boarding school Manbaul Ulum Bondowoso. This research is field research with a qualitative approach. Data were obtained by using data collection instruments in the form of observation, documentation, and interviews. Then the data were analyzed with qualitative data analysis of the Miles and Huberman model. The validity of the data was tested by triangulation. The results showed that first, the Manbaul Ulum Islamic boarding school developed a pesantren learning curriculum based on maqashid shari'ah and not only on nushus shari'ah, which in this case has the principles of Tawazun, I'tidal, and Tawassuth in thinking and acting; second, the curriculum developed at the Manbaul Ulum Islamic boarding school is oriented to build religious moderation in the students so that they can preach it after associating with the wider community. Keywords: Islamic Education Curriculum, Manbaul Ulum Islamic Boarding School, Religious Moderation